2018
DOI: 10.1128/aac.01814-17
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Fluoroquinolone Susceptibility Directly from Whole-Genome Sequence Data by Using Liquid Chromatography-Tandem Mass Spectrometry To Identify Mutant Genotypes

Abstract: Fluoroquinolone resistance in Gram-negative bacteria is multifactorial, involving target site mutations, reductions in fluoroquinolone entry due to reduced porin production, increased fluoroquinolone efflux, enzymes that modify fluoroquinolones, and Qnr, a DNA mimic that protects the drug target from fluoroquinolone binding. Here we report a comprehensive analysis, using transformation and mutant selection, of the relative importance of each of these mechanisms for fluoroquinolone nonsusceptibility using as a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…The highest MIC was against the ompK36 mutant, but it remained meropenem/vaborbactam susceptible. This was expected, since it has been shown that meropenem/vaborbactam resistance in derivatives of K. pneumoniae clinical isolates is primarily caused by ompK36 loss in a background where ompK35 has already been lost (19) and we have previously reported that Ecl8 actually produces more OmpK35 than clinical isolates (29).…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…The highest MIC was against the ompK36 mutant, but it remained meropenem/vaborbactam susceptible. This was expected, since it has been shown that meropenem/vaborbactam resistance in derivatives of K. pneumoniae clinical isolates is primarily caused by ompK36 loss in a background where ompK35 has already been lost (19) and we have previously reported that Ecl8 actually produces more OmpK35 than clinical isolates (29).…”
Section: Resultsmentioning
confidence: 79%
“…K. pneumoniae clinical isolate KP21 produces low levels of OmpK35 (29). Experimentally, it has been shown that ramR loss of function downregulates OmpK35 production in K. pneumoniae (27) and KP21 carries a frameshift mutation in ramR (29) whilst whole genome sequencing confirmed that ompK35 itself is wild type.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because FQ3 is derived from Ecl8, a laboratory strain, and because FQ3 carries mutations that increase efflux pump production (9), we wanted to test the impact of kvrA inactivation in a wild-type clinical isolate. To do this, we insertionally inactivated kvrA (as above) in the susceptible K. pneumoniae clinical isolate S17, which has wild-type envelope permeability (26) and showed by LC-MS/MS that OmpF and OmpC levels fell in this mutant relative to S17, as seen in FQ3. Porin abundance did not change upon nlpD inactivation in S17, also as seen in FQ3 (Fig.…”
Section: Textmentioning
confidence: 99%
“…In contrast, meropenem/vaborbactam MICs against the kvrA and ompK36 mutants were 1 µg.mL −1 (four doublings higher than against S17) and 32 µg.mL −1 respectively (Table 4). Hence, even in an otherwise wild-type KPC-producing clinical K. pneumoniae isolate (26), OmpK35/OmpK36 downregulation caused solely by kvrA mutation is enough to reduce meropenem/varborbactam susceptibility.…”
Section: Textmentioning
confidence: 99%